Intelligent Health Policy Theory, Concept and Practice - Virtanen, Petri (Springer International Publishing, 2018)
This book provides a general overview of intelligence in health policy, health-care organizations and health services in the light of the current EU digital agenda, which aims to make health data and e-health tools publicly available. The first part analyses the implications of knowledge management and decision-making procedures for intelligent health policies and governance. The second part discusses in detail the concept of intelligence and illustrates why the perspective of organizational intelligence offers a solution to contemporary problems in health care, while the third part focuses on intelligent leadership models in health-care organizations. Providing a guide to new ways of understanding, developing, and reforming health policy and health services, it appeals to scholars as well as decision-makers in health governance and health-care institutions. .